PERAN END CHILD PROSTITUTION AND TRAFFICKING (ECPAT) DALAM MENANGANI ONLINE CHILD SEXUAL EXPLOITATION PADA MASA PANDEMI COVID-19 DI INDONESIA - Jannah, Annisa Raudhatul; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research explains the role of the international organization Ending the Sexual Exploitation of Children (ECPAT) in handling cases of online child sexual exploitation in Indonesia. Since the COVID-19 pandemic, children who learn through the internet are increasingly vulnerable to sexual exploitation crimes in the digital world. Therefore, ECPAT Indonesia as part of an international organization is present to assist in handling and preventing these crimes by focusing on handling cases of online child sexual exploitation, taking the role of conducting various programs and collaborating with government and non-government institutions to tackle the problem of online child sexual exploitation. This research aims to find out how the role played by ECPAT in handling cases of online child sexual exploitation in Indonesia in 2019-2021. This research uses the theory of the role of International Organizations and qualitative research methods with research techniques interviews with international actors who are used as objects of research, and is complemented by literature study, which utilizes secondary data obtained through literature studies obtained from various literature such as books, journals, bulletins, newspapers, annual reports of several related agencies, documents, or other materials that support research. ECPAT in tackling online child sexual exploitation has a strategy in running its program, namely through research, policy advocacy, building networks, and socialization to the community. The roles that ECPAT has played include conducting research or collecting data related to child exploitation, advocating to the government or related parties, training with related institutions with the aim of being better prepared to deal with the problem of child sexual exploitation, and socializing campaigns, workshops, or online educational seminars. Keywords: Role, ECPAT, Online Child Sexual Exploitation